The science of food : an introduction to food science, nutrition and microbiology - Gaman, P. M.; Sherrington, K. B. (Pergamon international library of science, technology, engineering, and social studies., 1981)
The Science of Food: An Introduction to Food Science, Nutrition and Microbiology, Second Edition conveys basic scientific facts and principles, necessary for the understanding of food science, nutrition, and microbiology. Organized into 17 chapters, this book begins with a discussion on measurement, metrication, basic chemistry, and organic chemistry of foods. Nutrients such as carbohydrates, fats, proteins, vitamins, mineral elements, and water in food are then described. The book also covers aspects of food poisoning, food spoilage, and food preservation. This book will be useful to students.